Stress coping strategies as mediators: toward a better understanding of sexual, substance, and delinquent behavior-related risk-taking among transition-aged youth - Dariotis, Jacinda K. (Deviant behavior, 2022)
Transitional aged youth (18-24) report increasing and peaking risk-taking (sexual, substance, and delinquent behavior). Stressful life events (SLE) are associated with these risk-taking behaviors. Little is known regarding what mediates these relationships. This study tests whether various coping strategies mediate the relationship between SLE and risky behavior in three domains among 18-24 year olds (N = 126; M age = 21.3, SD = 1.9; 52% Black; 56% female). After adjusting for covariates and simultaneously modeling two stress variables, only stressful life events, but not perceived stress, was uniquely associated with risk-taking behaviors at moderate to high levels. Significant indirect effects of SLE via avoidance coping were found for illicit drug use both concurrently and prospectively and for risky sex concurrently. For participants reporting greater stressful life experiences, substance use and risky sex behaviors become greater as avoidance coping increases. Avoidance coping was a partial mediator for the concurrent relationship between stressful life events and substance use/risky sex, but a full mediator for the prospective relationship between stressful life event and substance use. None of the coping strategies mediate the relationship between stressful life events and delinquency. Prevention and intervention strategy implications for reducing avoidance coping and promoting alternative coping styles are discussed.